Law and disorder in the postcolony - Comaroff, Jean; Comaroff, John L., 1945- (University of Chicago Press, 2006)
Are postcolonies haunted more by criminal violence than other nation-states? The usual answer is yes. In Law and Disorder in the Postcolony, Jean and John Comaroff and a group of respected theorists show that the question is misplaced: that the predicament of postcolonies arises from their place in a world order dominated by new modes of governance, new sorts of empires, new species of wealth?an order that criminalizes poverty and race, entraps the?south? in relations of corruption, and displaces politics into the realms of the market, criminal economies, and the courts. As these essays make.